Accelerating Chrysomya Megacephala Maggot growth for forensic entomology cases - Mohd Iswadi Ismail; Khairul Osman; Ong, Hua King; Nurhaslina Hassan; Ezlan Elias; Kaswandi Md.Ambia; Ahmad Rohi Ghazali; Jamaludin Mohamed; Baharuddin Hj.Omar (penerbit ukm, 2007)
Forensic entomology is defined as knowledge about insect and its relationship with a decomposed human body. With this knowledge, post-mortem interval Jurnal Sains Kesihatan Malaysia 5 (1) 2007: 17-2618(PMI) can be estimated. PMI can be determined by taking into consideration the insect species and the developmental stage of the insects. Identification of the insect species requires the insect to develop into adulthood. Since this will take a relatively long time, the objectives of this study were to optimize temperature and humidity for the growth of Chrysomya megacephala larvae to adults. C. megacephala larvae were transferred into a rearing container and put inside a special incubator with temperature adjusted to 27, 30, 33, 36 and 39°C separately. Once optimum temperature for larvae growth was determined, optimum relative humidity was determined then for the length of time taken for C. megacephala larvae to develop into adults. To achieve this, the larvae of C. megacephala were incubated in a special incubator and the relative humidity set at 54.2, 57.6, 76.0 and 67.5% (control) separately. The developmental stages of C. megacephala for both temperatures and humidity levels were recorded accordingly. Results obtained indicated that C. megacephala developmental stages grew much faster in 33oC than other temperatures. The optimum relative humidity level for the species was 76.0%. By utilizing the appropriate temperature and relative humidity the development of C. megacephala, from eggs to adults could be reduced from 8 to 9 days to 5 days.